Potential for the anaerobic oxidation of benzene and naphthalene in thermophilic microorganisms from the Guaymas Basin - Zehnle, Hanna; Otersen, Carolin; Benito Merino, David; Wegener, Gunter (Frontiers in Microbiology, 2023)
Unsubstituted aromatic hydrocarbons (UAHs) are recalcitrant molecules abundant in crude oil, which is accumulated in subsurface reservoirs and occasionally enters the marine environment through natural seepage or human-caused spillage. The challenging anaerobic degradation of UAHs by microorganisms, in particular under thermophilic conditions, is poorly understood. Here, we established benzene-and naphthalene-degrading cultures under sulfate-reducing conditions at 50 °C and 70 °C from Guaymas Basin sediments. Dependent on the combination of UAH and temperature, different microorganisms became enriched. A Thermoplasmatota archaeon was abundant in the benzene-degrading culture at 50 °C, but catabolic pathways remained elusive, because the archaeon lacked most known genes for benzene degradation. Two novel species of Desulfatiglandales bacteria were strongly enriched in the benzene-degrading culture at 70 °C and in the naphthalene-degrading culture at 50 °C. Both bacteria encode almost complete pathways for UAH degradation and for downstream degradation. They likely activate benzene via methylation, and naphthalene via direct carboxylation, respectively. The two species constitute the first thermophilic UAH degraders of the Desulfatiglandales. In the naphthalene culture incubated at 70 °C, a Dehalococcoidia bacterium became enriched, which encoded a partial pathway for UAH degradation. Comparison of enriched bacteria with related genomes from environmental samples indicated that pathways for benzene degradation are widely distributed, while thermophily and capacity for naphthalene activation are rare. Our study highlights the capacities of uncultured thermophilic microbes for UAH degradation in petroleum reservoirs and in contaminated environments.